Eating disorders among athletes: causes, symptoms, and health consequences - Mikulska, Jowita; Lewandowski, Mikołaj; Kurkiewicz, Wojciech; Woźniak, Oskar; Wąsik, Joanna; Gryboś, Kacper; Sepioło, Weronika; Kiełbratowska, Julia; Kwiatkowska, Zofia (Quality in Sport, 2025)
A review of the literature on the most common eating disorders among athletes, their causes, impact on physical and mental health, and difficulties associated with diagnosis and treatment. Introduction: Eating disorders are a group of serious psychiatric conditions that include anorexia nervosa, bulimia, binge eating disorder (BED), orthorexia and muscle dysmorphia. These disorders are characterized by abnormal eating behaviors that can severely impact both physical and mental health. Research indicates that athletes, particularly those involved in strength or aesthetic sports, are at a higher risk for developing these issues compared to non-athletes. This highlights the importance of addressing eating disorders within the context of public health. This review aims to explore the definition of eating disorders, their symptoms, risk factors, especially those specific to athletes, and the available treatment options. Purpose of study: This is a review of the literature on the most common eating disorders among athletes, their causes, impact on physical and mental health, and difficulties associated with diagnosis and treatment. Materials and methods: The literature review was based on materials retrieved from the PubMed and Google Scholar databases, using keywords such as “eating disorder” AND “sports”, “eating disorders in athletes”, “eating disorders causes”, and “eating disorders treatment”. The scope of the studies analyzed covered the years 2005 to 2024. Conclusion: Athletes, especially women and those involved in strength or aesthetic sports, are at a higher risk of developing eating disorders. Among athletes, there are specific symptoms of eating disorders, such as reduced energy availability, which can lead to conditions like RED-S (Relative Energy Deficiency in Sport) and the Female Athlete Triad. Effective treatment for these disorders should focus on early recognition, with particular attention to early symptoms. Treatment involves both non-pharmacological methods, such as cognitive-behavioral therapy and PED-T (Physical Exercise and Diet Therapy), as well as interventions to correct nutritional deficiencies and pharmacotherapy.